2017
DOI: 10.1002/uog.15978
|View full text |Cite
|
Sign up to set email alerts
|

Changes in uterine artery Doppler velocimetry and circulating angiogenic factors in the first half of pregnancies delivering a small‐for‐gestational‐age neonate

Abstract: First- and second-trimester UtA Doppler velocimetry and maternal circulating angiogenic markers have clinical utility as a cross-sectional assessment for the identification of pregnancies at high risk of delivering a SGA neonate, however, they do not improve prediction when their longitudinal changes are used. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 42 publications
2
27
0
1
Order By: Relevance
“…In accordance with previous studies 3740 , we found, that an increased mean UtA-PI at <24 weeks of gestation was mainly associated with late SGA and with SGA at birth. Recent findings suggest that interrogation of fetal vessels at 20–24 weeks of gestation may also play a role in the identification of subsequent development of SGA.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with previous studies 3740 , we found, that an increased mean UtA-PI at <24 weeks of gestation was mainly associated with late SGA and with SGA at birth. Recent findings suggest that interrogation of fetal vessels at 20–24 weeks of gestation may also play a role in the identification of subsequent development of SGA.…”
Section: Discussionsupporting
confidence: 93%
“…Three more had unclear risk of bias in the same category and one had unclear risk of bias in patient selection. The rest of the studies had low risk of bias in all categories. Figures S1 and S2 show risk of bias in the included studies, according to the QUADAS‐2 tool for diagnostic test accuracy reviews.…”
Section: Resultsmentioning
confidence: 99%
“…Mean maternal age at evaluation was 32.2 (SD 1.3) years and mean maternal BMI was 23.4 (SD 1.7) kg/m 2 . Among studies evaluating suspected SGA (numbers are not mutually exclusive), 28% (460/1641) of cases had composite adverse perinatal outcome, 25.9% (555/2147) required admission to the neonatal unit, 17% (187/1102) had CS‐IFC, 1.7% (12/725) had 5‐min Apgar score < 7, 6.1% (78/1279) had neonatal acidosis and 2.7% (5/185) had perinatal death. Among studies evaluating SGA neonates (numbers are not mutually exclusive), 29.7% (265/891) of cases had composite adverse perinatal outcome, 18.6% (165/888) required admission to the neonatal unit, 12.5% (465/3727) had CS‐IFC, 1.8% (65/3540) had 5‐min Apgar score < 7, 3.5% (83/2372) had neonatal acidosis and 0.7% (26/3562) had perinatal death.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, similar positive findings have been reported for conditional centiles of EFW, though these findings are contested in more recent studies 11,31,46 . The relationship of longitudinal changes with perinatal outcome in early-onset FGR is sparsely reported [47][48][49] . Some have suggested worse outcome in early-onset growth-restricted fetuses with resolution of cerebral redistribution 48 .…”
Section: Interpretation Of Study Findings and Comparison With Publishmentioning
confidence: 99%